Establishing and promoting an 'out-of-area' programme for GP placements as a strategy to expand undergraduate experience in primary care. (2022) - Cooper, Max; Jegatheesan, Menaka; Sornalingam, Sangeetha; Sharp, Harriet; Fernandes, Carl
No abstract available